Changes in high sensitivity serum CRP under periodontal therapy and its association with the depth of pathological periodontal pocket - Al-Bayati, Lina; Kamil, Wisam; Habashnah, Rola; Abbood, Lina H. (2011)
Periodontitis is a chronic inflammatory disease, elicited by a complex mixture of anaerobic, Gram-negative bacteria that result in the destruction of the supporting structures of the dentition (Pihlstrom et al, 2005). This disease affects the majority of population (Brown et al, 1996) and the periodontal tooth mortality was reported by Ong, 1998 to be associated with the loss of periodontal attachment. C-reactive protein, as an acute-phase reactant, currently being labelled as a possible risk indicator for future cardiac events, and it is elevated in periodontitis patients compared to controls (Ebersole et al, 1997). Despite the fact for effectiveness of periodontal treatment in modifying the level of serum levels of C-reactive protein (CRP) and interleukin-6 (IL-6) (Ebersole et al., 1997, Mattila et al., 2002), incomplete or inadequate treatment of extensive periodontal disease will not be expected to have a significant impact on systemic mediators (Ioannidou et al., 2006). The aim of this study was to explore the outcomes of periodontal therapy in terms of changes in C-reactive protein (CRP) and its effect on the depth of pathological periodontal defect. Following protocol review and approval by Institutional Review Board of Jordan university of science and technology, a total of fifty five periodontitis patients randomly distributed into either a treatment group (37 patients) received non-surgical periodontal therapy with intensive oral hygiene nstructions and repeated therapy course for residual bleeding periodontal pockets or control group (18 patients) received delayed periodontal treatment after completion of clinical trial evaluation. Medical history, demographic data and clinical periodontal parameters and C-reactive protein were collected at baseline and three months at reassessment appointments. The results showed statistically significant improvements for all periodontal clinical parameters, and significant reduction of hs-CRP levels (p=0.003) after the treatment regime within the tested treatment group compared to control patients, and there was a significant positive correlation (p=0.006, r=0.411) between elevated serum levels of CRP and deep pathological periodontal pockets.